Mathematics

# Resolve into partial fraction $\displaystyle \frac{x^3-3x-2}{(x^2+x+1)(x+1)^2}$

$\displaystyle \frac{3x-1}{x^2+x+1}+\frac{2}{(x+1)^2}-\frac{3}{(x+1)}$

##### SOLUTION
Let $\displaystyle \frac { x^{ 3 }-3x-2 }{ \left( x^{ 2 }+x+1 \right) \left( x+1 \right) ^{ 2 } } =\frac { Ax+B }{ x^{ 2 }+x+1 } +\frac { C }{ x+1 } +\frac { D }{ { \left( x+1 \right) }^{ 2 } }$
$\Rightarrow { x }^{ 3 }-3x-2=\left( Ax+B \right) { \left( x+1 \right) }^{ 2 }+C\left( x^{ 2 }+x+1 \right) \left( x+1 \right) +D\left( x^{ 2 }+x+1 \right) \\ \Rightarrow { x }^{ 3 }-3x-2=A\left( { x }^{ 3 }+2{ x }^{ 2 }+2x \right) +B\left( { x }^{ 2 }+2x+1 \right) +C\left( { x }^{ 3 }+2{ x }^{ 2 }+2x+1 \right) +D\left( x^{ 2 }+x+1 \right)$
On comapring coefficients we get
$A+C=1,2A+B+2C+D=0,2A+2B+2C+D=-3,B+C+D=-2\\ \Rightarrow A=3,B=-1,C=-3,D=2$
Hence
$\displaystyle \frac { x^{ 3 }-3x-2 }{ \left( x^{ 2 }+x+1 \right) \left( x+1 \right) ^{ 2 } } =\frac { 3x-1 }{ x^{ 2 }+x+1 } +\frac { -3 }{ x+1 } +\frac { 2 }{ { \left( x+1 \right) }^{ 2 } }$
Hence, option 'A' is correct.

Its FREE, you're just one step away

Single Correct Medium Published on 17th 09, 2020
Questions 203525
Subjects 9
Chapters 126
Enrolled Students 84

#### Realted Questions

Q1 Subjective Medium
$\displaystyle \int { \cos{ \pi }xdx=? }$

Asked in: Mathematics - Integrals

1 Verified Answer | Published on 17th 09, 2020

Q2 Single Correct Medium
If $\displaystyle\int { \sqrt { 1+\sin { x } } \cdot f\left( x \right) dx } =\dfrac { 2 }{ 3 } { \left( 1+\sin { x } \right) }^{ { 3 }/{ 2 } }+C$, then $f\left( x \right)$ is equal to
• A. $\sin { x }$
• B. $\tan { x }$
• C. $1$
• D. $\cos { x }$

Asked in: Mathematics - Integrals

1 Verified Answer | Published on 17th 09, 2020

Q3 Single Correct Medium
$\underset{0}{\overset{\pi / 2}{\int}} \, \log \, \cot \, x \, dx =$
• A. $1$
• B. $\pi$
• C. $\dfrac{\pi}{2}$
• D. $0$

Asked in: Mathematics - Integrals

1 Verified Answer | Published on 17th 09, 2020

Q4 Subjective Medium
$\int \ sinx.\ cosx \;dx$

Asked in: Mathematics - Integrals

1 Verified Answer | Published on 17th 09, 2020

Q5 Subjective Hard
Integrate $\displaystyle \int \frac{3x-1}{(x-1)(x-2)(x-3)}dx$

Asked in: Mathematics - Integrals

1 Verified Answer | Published on 17th 09, 2020